Teoria dos Grafos no ensino médio: aplicações em problemas de trânsito - Torre, João Paulo Gonçalves Della (Universidade Federal de São Carlos, 2018)
This work, explores through the methodologies: Problem Solving and Mathematical Modeling, concepts of Graph theory in the second year of the High School of a State School. The concepts developed here in a contextualized way, aim to lead the students to experience con- tent not present in the curriculum, but that can be used to explain and solve everyday problems.
Theory of Graphs in high school: applications in traffic problems
Keywords: Resolução de problemas; Modelagem; Ensino; Aprendizagem; Grafos; Contextualização; Resolución de problemas; Modelado; Enseñanza; Aprendizaje; Grafos; Contextualización; Problem solving; Modeling; Teaching; Learning; Graphs; Contextualization; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO